Effect of replacing fish meal by fenugreek seed meal on growth performance of African cat fish - Shaikhlar, A.; Alimon, Abdul Razak; Daud, M. Hassan (2011)
A 10-week of feeding experiment was conducted for assay a total and partial replacement of fish meal (FM) with fenu greek seed (Trigonella foenum-graecum) meal (FSM) in the feeds for African cat fish (Clarias gariepinus). Triplicate groups of fish (initial body weight 9.3 g /fish) were fed five isonitrogenous and isocaloric diets of 35% digestible protein and 300 kcal/100g of digestible energy. The control diet contained 14.2% fish meal and 0 FSM, whereas in the other four diets, FM considered 10.7, 7.1, 3.6 and 0% and FSM 10, 20, 30 and 40% of those diets. Considering the influence of experimental diet on growth performance, final body weight (FBW) and specific growth rate (SGR) of the fish fed diets containing 20 and 30% FSM were comparable to the fish fed the control diet. Fish fed the diet containing FSM-40% recorded the lowest fish growth (P < 0.05) compared with the control and other treatment groups. Feed conversion ratio was lowest for the FSM-20% and FSM-30% groups, while the highest values were belonged to the FSM-40%. Present research concluded that the optimum growth performance and feed consumption could be reached with the replacement of FSM (30%) in the diet of African catfish.